2015
DOI: 10.1371/journal.pone.0130625
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cranial Structure, Biomechanical Performance and Ecological Diversity in Varanoid Lizards

Abstract: Skull structure is intimately associated with feeding ability in vertebrates, both in terms of specific performance measures and general ecological characteristics. This study quantitatively assessed variation in the shape of the cranium and mandible in varanoid lizards, and its relationship to structural performance (von Mises strain) and interspecific differences in feeding ecology. Geometric morphometric and linear morphometric analyses were used to evaluate morphological differences, and finite element ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…As well as qualitative visual comparisons, 95% values were generated using the R code following the methods of McCurry et al (2015b) and Walmsley et al (2013b). These values represent the peak strain within the model if the top 5% of strain values are removed.…”
Section: Finite Element Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as qualitative visual comparisons, 95% values were generated using the R code following the methods of McCurry et al (2015b) and Walmsley et al (2013b). These values represent the peak strain within the model if the top 5% of strain values are removed.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…Finite element analysis is a modeling technique that can predict the response of complex structures to applied load using numerical methods. Previous studies using this technique have shown that the cranial morphology of a species often relates to its preferences in feeding (Dumont et al, 2005;McCurry et al, 2015b;McHenry et al, 2007;Moreno et al, 2008;Soons et al, 2010). Here we aim to use finite element analysis to: 1) Determine whether longirostry has similar effects on structural performance during biting, shaking and twisting in crocodilians and odontocetes.…”
Section: Introductionmentioning
confidence: 99%
“…The Varanus cranium is a broad, mediolateral and highly fenestrated braced frame (McCurry et al, 2015) and supports its braincase with various skeletal elements such as the epipterygoids (Metzger, 2002), muscular elements such as the protractor musculature (Holliday and Witmer, 2008;Moazen et al, 2009), and a complex network of cranial joints (Holliday and Witmer, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…FEA has been used to explore hypotheses of cranial form and function (e.g. Soons et al, 2010;Santana and Dumont, 2011;McCurry et al, 2015), and the effects of soft tissue on non-mobile cranial joints (e.g. Curtis et al, 2013;Jones et al, 2017), and to create artificial morphologies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This facilitates standardization between specimens of different size via Procrustes superimposition and permits visualizations that aid interpretation. Over the past decade, geometric morphometrics has become an increasingly accessible approach for morphological analyses and has been used to characterize and compare shape variation amongst two-dimensional images of reptile skulls (e.g., Stayton, 2005;Jones, 2008;Meloro and Jones, 2012;Sanger et al, 2013;Fabre et al, 2014;Openshaw et al, 2016); however, it also has been applied to three-dimensional reptile anatomy using X-ray computed tomography (CT) (Parr et al, 2012;McCurry et al, 2015). In at least one case, it has been used as an approach to associate fossils with modern taxa (Dollion et al, 2015).…”
mentioning
confidence: 99%